2017
DOI: 10.1597/15-010
|View full text |Cite
|
Sign up to set email alerts
|

Ear Infection in Isolated Cleft Lip: Etiological Implications

Abstract: Background and Hypothesis Chronic ear infections are a common occurrence in children with orofacial clefts involving the secondary palate. Less is known about the middle ear status of individuals with isolated clefts of the lip, although several studies have reported elevated rates of ear infection in this group. The purpose of this retrospective study was to test the hypothesis that chronic ear infections occur more frequently in isolated cleft lip cases (n=94) compared with controls (n=183). Methods A ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This finding was consistent with the literature data [24,26,32]. Hence, we can confirm the severity of congenital disorder of the maxillofacial region that directly affects the state of local microbiota [26,34].…”
Section: Discussionsupporting
confidence: 93%
“…This finding was consistent with the literature data [24,26,32]. Hence, we can confirm the severity of congenital disorder of the maxillofacial region that directly affects the state of local microbiota [26,34].…”
Section: Discussionsupporting
confidence: 93%
“…Children with CLP may suffer recurrent or continuous OME, which can lead to atelectasis, ossicular fixation, and/or tympanosclerosis [3,33,34]. The risk of chronic ear infection may be higher even in children with isolated cleft lip cases compared with unaffected controls [35]. The ear problems can result in conductive hearing loss of up to 30 decibels (dB).…”
Section: Consequences Of Ome In Clpmentioning
confidence: 99%
“…Interestingly though only one case of cleft lip was affected in our study, in a study by Ruegg et al, 31% of cleft lip cases had ear infection compared to 11% controls. 19 Flynn et al, also reported significantly lower prevalence of MEDs in CP. 7 In present study MEDs were more common in non-operated cases (46 out of 51) compared to operated cases (24 out of 49) who underwent surgical repair of cleft lip and palate and association was significant with p<0.001.…”
Section: Discussionmentioning
confidence: 91%